SYSTEMATIC REVIEW WITH COMPARATIVE ANALYSIS OF RECOMMENDATIONS FOR THE DIAGNOSIS OF NONALCOHOLIC FATTY LIVER DISEASE - N.A. TOKTOGULOVA (Avicenna Tajik State Medical University, 2021)
A review of the available literature has shown that the current epidemic of nonalcoholic fatty liver disease (NAFLD) is closely related with the widespread prevalence of metabolic risk factors worldwide, such as obesity, type 2 diabetes, and dyslipidemia. In parallel with the increasing availability of effective antiviral drugs, NAFLD is rapidly becoming the most common cause of chronic liver disease in Western countries, and a similar trend is expected in Eastern countries in the coming years. This epidemic and its aftermath have prompted experts from around the world to identify effective strategies for the diagnosis, management and treatment of NAFLD. Various scientific associations from America, Europe and the Asia-Pacific region have offered recommendations based on the most recent data on NAFLD. These recommendations are consistent with the key elements of NAFLD management, but at the same time, there are significant differences in some critical points. We have identified clinical guidelines from 8 different scientific societies with a worldwide reputation, and tried to conduct a systematic and comparative analysis of the presented protocols. Differences were noted in: definition of NAFLD, screening for NAFLD in high-risk patients, a non-invasive test proposed to diagnose NAFLD and identify NAFLD patients with severe fibrosis, follow-up protocols, and finally, treatment strategy